Susan J. Phatt. Losing Face. Status Politics in Japan. Berkeley, Los Ángeles y Oxford, University of California Press, 1990 - Cejas, Mónica (Estudios de Asia y África, 1995)
Susan J. Pharr. Losing Face. Status Politics in Japan. Berkeley, Los Ángeles y Oxford, University of California Press, 1990.